Analysis of Education, Organizational Commitment, and Discipline on Leadership at the Department of Population and Civil Registration of Medan City - Ahmad Rifai; Teguh Wahyono; Ikhah Malikhah (Universitas Dehasen Bengkulu, 2026)
This research aims to analyze the influence of education, organizational commitment, and work discipline on leadership at the Department of Population and Civil Registration (Disdukcapil) of Medan City. The background of the study is based on the fact that leadership implementation is still not optimal, as indicated by weak leadership abilities in providing direction, communication, and motivation, as well as the failure to achieve targets in several population administration services. This study uses a quantitative approach with a causal method, in which the population as well as the sample consists of all 60 employees of the Medan City Disdukcapil, using a saturated sampling technique. Data were collected through questionnaires, observation, and interviews, and then analyzed using multiple linear regression analysis. The results of the study are expected to provide an empirical overview of the extent to which education, organizational commitment, and work discipline influence leadership, both partially and simultaneously. The findings of this research are also expected to serve as a consideration for the Medan City Disdukcapil in improving leadership quality and organizational performance through strengthening employee education, increasing organizational commitment, and enforcing work discipline.